Aphyllorchis maliauensis (orchidaceae), a new species from the Maliau Basin, Sabah, Borneo - Kenji Suetsugu; Monica Suleiman; Florina Anthony; Hirokazu Tsukaya (Magnolia Press, 2018)
Aphyllorchis Blume (1825: 16) comprises approximately 30 species distributed from Sri Lanka, the western Himalayas, and China through Indochina, Malaysia, Indonesia, Taiwan and the Philippines eastward to New Guinea and Australia (Hsieh et al. 2013, Tian et al. 2013). Aphyllorchis species are leafless and mycoheterotrophic, with erect, unbranched stems, racemose inflorescences, multiple resupinate flowers, petals similar to sepals but shorter and narrower and lips divided into hypochile and epichile (Tian et al. 2013). As in most other mycoheterotrophs (Suetsugu 2017, Suetsugu & Nishioka 2017, Suetsugu et al. 2017), the diversity of Aphyllorchis species could be underestimated since the short flowering season and inconspicuous habit make them easily overlooked in the wild (Hsieh et al. 2013).